A Promising Listeria-Vectored Vaccine Induces Th1-Type Immune Responses and Confers Protection Against Tuberculosis - Yin, Yuelan; Lian, Kai; Zhao, Dan; Tao, Chengwu; Chen, Xiang; Tan, Weijun; Wang, Xiaobo; Xu, Zhengzhong; Hu, Maozhi; Rao, Yan; Zhou, Xiaohui; Pan, Zhiming; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Deaths associated with tuberculosis (TB) is rising and accounted for 1.4 million deaths in 2015 many of which were due to drug-resistant bacteria. Vaccines represent an important medical intervention, but the current Bacilli Calmette-Guerin (BCG) vaccine is not ideal for the protection of teenagers and adults. Therefore, a safe and effective vaccine is urgently needed. In this study, we designed a novel vaccine using an attenuated Listeria monocytogenes strain carrying fusion antigen FbpB-ESAT-6 (rLM) and characterized its safety and protective efficacy against Mycobacterium tuberculosis (M.tb) infection in mice. Compared to the wild type strain yzuLM4 and parental strain LMΔactA/plcB (LM1-2), the virulence of rLM was significantly reduced as judged by its infectious kinetics and LD50 dose. Further characterization of intravenous immunization showed that prime-boost vaccination significantly increased the levels of Th1 cytokines (IFN-γ, IL-17, and IL-6), and enhanced cytotoxic T lymphocyte (CTL) CTLs activity, suggesting that rLM could elicit potent Th1/Th17 responses. More importantly, rLM significantly conferred the protection against M.tb H37Rv challenge. Collectively, our findings indicated that rLM is a novel and useful tool to prevent M.tb infection, and can be potentially be used to boost BCG-primed immunity.